2015
DOI: 10.1186/s12865-015-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory test based on determination of cytokine profiles: a promising assay to identify exposition to contact allergens and predict the clinical outcome in occupational allergic contact dermatitis

Abstract: BackgroundPara-phenylenediamine (PPD) is the main allergen causing adverse reactions to hair dyes and a frequent cause of occupational-related skin sensitization among hairdressers and beauticians. The immunologic mechanism of the disease relies on the production of inflammatory cytokines by allergen-specific T cells, while regulatory T cells are thought to down-modulate the allergic response. This study was aimed at investigating the expression of effector or regulatory cytokines in exposed subjects in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Given the level of sensitivity, the number of false negatives, and interlaboratory variation, the lymphocyte transformation test seems very unlikely to be a replacement for patch testing, but does have the advantages that additional endpoints such as the identity of the proliferating cells (CD4 or CD8) or the nature of cytokine production can be incorporated to improve mechanistic understanding. 7,47,48 In addition to sensitization being associated with changes in the profile of naïve and effector/central memory and EMRA cells, we also observed that, particularly for extremely allergic individuals, the Treg frequency was decreased, as was the CD4 + /CD8 hi ratio, whereas CLA expression was increased. These findings appeared to be a feature of sensitization to each of the three different allergens, despite the fact that they have very different chemistries.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Given the level of sensitivity, the number of false negatives, and interlaboratory variation, the lymphocyte transformation test seems very unlikely to be a replacement for patch testing, but does have the advantages that additional endpoints such as the identity of the proliferating cells (CD4 or CD8) or the nature of cytokine production can be incorporated to improve mechanistic understanding. 7,47,48 In addition to sensitization being associated with changes in the profile of naïve and effector/central memory and EMRA cells, we also observed that, particularly for extremely allergic individuals, the Treg frequency was decreased, as was the CD4 + /CD8 hi ratio, whereas CLA expression was increased. These findings appeared to be a feature of sensitization to each of the three different allergens, despite the fact that they have very different chemistries.…”
Section: Discussionmentioning
confidence: 58%
“…Cytokine expression profiling, including the ratio of IL-5 to IL-8 production 47 or the secretion of interferon-γ, are being explored currently. 48 Experience with PPD is rather more variable, with some groups reporting vigorous proliferative responses to free PPD (6 of 9 +++ patch test donors; 7 of 8 ++ or +++ patch test donors; and 10 of 11 donors said to have a strong history of sensitization to PPD). 11,12,24 However, other studies found that free PPD stimulated proliferative responses in a minority of donors (1/6), despite them having ++ or +++ scores in patch tests, 49 or that 0 of 9 sensitized donors reacted positively to free PPD, although 7 of 9 responded to the metabolite Brandowski's base.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic assays have also shown promise as diagnostic tools for ACD [10,11,12]. In particular, an ELISpot assay, which can detect serum levels of IL-4, IL-5, IL-10, IL-13, and IFN-γ, was developed for ACD diagnostics [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Pathogenesis of allergic contact dermatitis includes sensitization (or induction) and elicitation (or efferent) phases, which are innate (opposite to contact irritant dermatitis) [20]. It is established at present that cytokines are crucial in inflammation, including immuneinvolved dermatitis [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…The Th1 cells release of pro-inflammatory cytokines includes il-1α, il-1β, il-8, il-13, tnf-α, and granulocyte-macrophage colony-stimulating factor (GM-CSF). They increase the vascular permeability and cause swelling and redness associated with inflammation and immunologic reactions in skin exposed to irritants, also affect the proliferation and differentiation of keratinocytes and mediators of cellular infiltration [3,21,22].…”
Section: Discussionmentioning
confidence: 99%